Exploring Vocabulary Learning Through Paper flashcards in a Rural Indonesian Junior High School - Ida Farida; Ali Muhtadi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aimed to explore the effectiveness of using paper flashcards in English vocabulary learning among seventh-grade junior high school students in rural areas. Vocabulary mastery is an essential aspect of English learning; however, limited learning media and low student engagement remain major challenges. The study employed a descriptive method using a mixed-method approach involving 32 students. Qualitative data were collected through classroom observations, while quantitative data were obtained from questionnaires and vocabulary tests. Data were analyzed using descriptive statistics and qualitative analysis, then integrated to provide a comprehensive understanding of the findings. The results revealed that the use of paper flashcards encouraged active student engagement in individual, pair, and group activities. The media also received positive responses regarding ease of use, visual attractiveness, and usefulness in learning. The normalized gain (N-gain) score of 0.71 was categorized as high, indicating a substantial improvement in students’ vocabulary mastery. The consistency among observation, questionnaire, and test results demonstrated that paper flashcards support active, interactive, and meaningful vocabulary learning, particularly in resource-limited school contexts. These findings suggest that simple paper-based media can serve as an effective alternative for improving student engagement and learning outcomes in English language learning.